The possibility of sex identification in beluga (Huso huso) by using PCR-RAPD technique - Keyvan shokoo, S.; Pourkazemi, M.; Kalbasi, M.R. (2004)
The goal of this study was to find a sex-specific DNA sequences in the male and female genomes of beluga (Huso huso), by random amplified polymorphic DNA (RAPD) assays performed on pooled DNA samples. Of the 310 different primers was tested, 7 primers produced no band. The most likely possibility is that PCR conditions have not been suitable for these 7 primers. It is also possible that these RAPD primers did not find suitable binding position to generate fragments. A single band was produced by primer 295 (OPT -17) which was specific to the male DNA. Further analysis of individual male and female beluga demonstrated that this primer yeilded a product that were in fact variable and reproducible, but were the result of variation in some individual males and females and not male-specific. Therefore, of the 4146 RAPDs scored, none were tightly linked to a sex-determining gene. The results support the idea that sex chromosomes are either not present or they weakly differentiated in the genome of beluga. Published